Behavioral Drivers of Buy Now Pay Later Over-Indebtedness in Indonesia - Marhaendro Purno; Muhammad Azizurrohman (Universitas Islam Negeri Ar-Raniry, 2026)
The rapid growth of Buy Now Pay Later (BNPL) services in Indonesia have transformed consumer access to digital credit while simultaneously raising concerns regarding impulsive borrowing and financial vulnerability. This study examines the psychological, perceptual, and cultural determinants of BNPL borrowing behavior, focusing on the roles of dark pattern exposure, impulsive buying tendency, perceived usefulness, perceived risk, and Islamic financial literacy. A quantitative cross-sectional survey was conducted among 587 Indonesian BNPL users between April and June 2025. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that exposure to dark patterns significantly increases impulsive buying tendency and perceived usefulness while reducing perceived risk, leading consumers to develop more favorable attitudes toward BNPL. Impulsive buying tendency, perceived usefulness, and attitudes toward BNPL were found to positively influence over-indebtedness intention, which subsequently increases repayment distress. Mediation analysis confirms that attitudes and borrowing intentions function as important psychological mechanisms linking cognitive perceptions and behavioral outcomes. In addition, Islamic financial literacy weakens the effects of impulsiveness and favorable attitudes on over-indebtedness intention, suggesting its role as a moral and cognitive safeguard within the Indonesian context. The study extends behavioral finance and financial technology literature by integrating manipulative interface design and religiously grounded financial literacy into consumer borrowing models. The findings also highlight the importance of ethical fintech design, transparent digital credit regulation, and culturally embedded financial education to support sustainable financial inclusion and reduce consumer financial vulnerability. ABSTRAK - Faktor Perilaku dalam Over-Indebtedness Buy Now Pay Later di Indonesia. Perkembangan pesat layanan Buy Now Pay Later (BNPL) di Indonesia telah mengubah pola akses masyarakat terhadap kredit digital, sekaligus menimbulkan kekhawatiran terkait perilaku berutang impulsif dan meningkatnya kerentanan keuangan. Penelitian ini mengkaji faktor-faktor psikologis, perseptual, dan kultural yang memengaruhi perilaku penggunaan BNPL, dengan fokus pada paparan dark patterns, kecenderungan pembelian impulsif, persepsi kegunaan, persepsi risiko, serta literasi keuangan syariah. Penelitian ini menggunakan pendekatan kuantitatif dengan desain survei potong lintang terhadap 587 pengguna BNPL di Indonesia selama periode April–Juni 2025. Analisis data dilakukan menggunakan metode Partial Least Squares Structural Equation Modeling (PLS-SEM). Hasil penelitian menunjukkan bahwa paparan dark patterns secara signifikan meningkatkan kecenderungan pembelian impulsif dan persepsi kegunaan, serta menurunkan persepsi risiko, sehingga membentuk sikap yang lebih positif terhadap BNPL. Kecenderungan pembelian impulsif, persepsi kegunaan, dan sikap positif terhadap BNPL terbukti meningkatkan niat berutang berlebihan (over-indebtedness intention), yang selanjutnya memperbesar tekanan pembayaran (repayment distress). Analisis mediasi mengonfirmasi bahwa sikap dan niat berutang berperan sebagai mekanisme psikologis penting yang menghubungkan persepsi kognitif dengan dampak keuangan yang merugikan. Selain itu, literasi keuangan syariah terbukti memperlemah pengaruh impulsivitas dan sikap positif terhadap niat berutang berlebihan, sehingga berfungsi sebagai pelindung moral dan kognitif dalam konteks masyarakat Indonesia. Penelitian ini memperluas kajian behavioral finance dan teknologi keuangan dengan mengintegrasikan desain antarmuka manipulatif dan literasi keuangan berbasis nilai keagamaan ke dalam model perilaku utang konsumen. Temuan ini menegaskan pentingnya desain fintech yang etis, regulasi kredit digital yang transparan, serta edukasi keuangan yang berakar pada nilai budaya untuk mendukung inklusi keuangan yang berkelanjutan dan mengurangi kerentanan keuangan konsumen.